FORMATION AND INSTALLATION OF RESTRICTIONS (ENCUMBRANCES) IN LAND USE - Dorosh, Y. M. (Land Management, Cadastre and Land Monitoring, 2013)
The peculiarities of the formation and establishment of restrictions (encumbrances) of land use are elucidated. Concept of territorial restrictions (encumbrances) and re‐ strictions (encumbrances) in land plots use are differentiated.